Composition and dimension dependent static and dynamic stabilities of inorganic mixed halide antimony perovskites. Issue 28 (25th June 2021) - Yang, Jack
Abstract : We systematically show that alloys of low-dimensional mixed-halide antimony perovskites exhibit weaker vibrational anharmonicity and electron–phonon coupling strengths, which may enhance their photo-stabilities compared to 3D halide perovskites. Abstract : Halide intermixing is an important approach to stabilise halide perovskites in the phase that gives the best optoelectronic properties, whereas replacing Pb is critical for eliminating the material toxicity to meet the requirements for domestic applications. Recently, all-inorganic lead-free Cs3 Sb2 I9 has emerged as a promising lead-free absorber, with its optoelectronic properties being further controllable by manipulating its structural dimensionality (0D or 2D) via composition engineering. In particular, superior photoconversion efficiency (up to 5%) under indoor illumination with high photostabilities have been demonstrated experimentally in 2D Cs3 Sb2 Cl y I9− y . To gain a more thorough understanding on how the properties of this family of materials are controlled by their chemistry and dimensionality, here, we employ density functional theory calculations to explore the phase stability, structural and electronic dynamics of Cs3 Sb2 X y I9− y (X = Br and Cl) across 74 different combinations of composition/dimensionality. The results show that Cs3 Sb2 X y I9− y alloys are predominantly stabilised by configurational entropy rather than enthalpy. In stark contrast to cubic inorganic lead/tin halide perovskites, Cs3 Sb2 X y I9− y are dynamically more stable at 300 K, as reflected by their low vibrational anharmonicities, the values of which also exhibit weak compositional dependency. This consequentially reduces the strength of electron–phonon couplings, thus enhancing the photoexcited carrier lifetime in these materials, which further demonstrates their promising potential to be integrated into indoor photovoltaic devices.